Psychological Distress Among a Tunisian Community Sample During the COVID-19 Pandemic: Correlations with Religious Coping - Fekih-Romdhane, Feten (Journal of religion and health, 2021)
Despite advances in medicine and technology, when facing epidemics people continue to turn to religion to deal with such unpredictable life-threatening events. We aimed to assess psychological distress in the general population of Tunisia during the COVID-19 pandemic and to examine the contribution of religious coping (RC) in the reports of anxiety and depression at the time of the survey. We carried out and online cross-sectional study using a non-probability snowball sampling technique. A total of 603 responses were recorded. The “Depression Anxiety Stress Scales,” the “Brief religious coping scale" and the “Arabic religiosity scale” were used. We found that 28.3%, 24.4% and 19.4% of the participants reported severe or extremely severe levels of depression, anxiety and stress, respectively. The mean score for positive RC was 22.8 ± 5.3, while that for negative RC was 14 ± 5.8. After controlling for confounders, multivariate analysis showed that negative RC significantly and positively contributed to depression and anxiety scores in our respondents, indicating that greater use of negative RC was associated with higher levels of psychological distress. No significant relationship was found between overall religiosity or positive religious coping and either depression or anxiety symptoms. Religious beliefs may have an impact on how people cope with emerging infectious disease outbreaks. Religion should be considered by professionals as an important variable to consider in therapy for individuals who engage in RC or perceive religious needs.